Yellow rust development on different wheat genotypes - Al-Maaroof, Emad Mahmood; Nori, Asoda Mohammed (Sulaimani Journal for Pure and Applied Sciences, 2018)
Yellow (Stripe) rust caused by Puccinia striiformis Westend, is currently considered as one of the most destructive foliar diseases of wheat in many wheat-growing areas in Iraq. The recent results of rust surveillance activities efforts showed that the epidemics of the disease have occurred annually in many wheat fields and caused significant decline in the national grain production. Yellow rust development were studied in seven different wheat genotypes with diverse levels of resistance and susceptibility under natural epidemics of the disease during two successive seasons in 2009 to 2011 at Bakrajo Experimental Station, Sulaimani. Results revealed that the highest disease development curve was recorded for SaberBeg, which resulted from 100% disease severity within 24 days, while the lowest value was recorded for Al-124 and resulted from 7.2% disease severity. Significant differences between the Areas under Disease Progress Curve (AUDPCs) values were also detected among the tested genotypes. AUDPCs values ranged from 13.8 to 311. The mean infection rate value in SaberBeg (0.312) was significantly surpassed all other wheat genotypes. Variations in infection rate and disease development curves among the genotypes were mainly attributed to the characteristics of P. striiformis pustules and uredospore’s on the tested genotype tissues. Significant differences in pustule size, number of pustules per unit area, inoculum load and dimension of uredospore were detected between the genotypes which were also reflected on the epidemic buildup of the disease on the tested genotypes.
Keywords: Stripe rust; Puccinia striiformis; Triticum aestivum; Epidemics; Fungal diseases